Formation of cyclopentane - methane hydrates in brine systems and characteristics of dissolved ions - Lv, Qiu-Nan; Li, Xiao-Sen; Chen, Zhao-Yang (Applied Energy, 2016)
BaSed on the hot brine in situ seafloor prepared for marine NGHs exploitation, the formation of hydrates and the characteristics of dissolved ions were investigated for the cyclopentane (CP)-methane-NaCl solution (3.5%) system. Both the gas consumption and the solution salinity influenced by two factors - the flow rate of gas (Q(g)) and the mass fraction of CP (M-CP)-were discussed. On one hand, the gas consumption went up at a lower Mcp (3.950 wt%) while dropped down at a higher M-CP (8.340 or 18.775 wt%) with the increase of Q(g). Nevertheless, higher mass fraction of CP behaved more favorable for the gas consumption. On the other hand, there would be a similar trend that the salinity of remaining liquid increased firstly and then decreased with the reaction time at any fixed Q(g) and M-CP, which might be attributed to the adsorption of Na+ and Cl- on the surface of hydrate. Furthermore, PXRD analysis of the hydrate was conducted to confirm this explanation. And it was confirmed that the ion of Na+ or Cl- did not play any role in the construction of hydrate cages. Meanwhile, CP was enclosed in large cavities (51264s) while CH4 was mainly enclosed in the small cavities (512). (C) 2016 Elsevier Ltd. All rights reserved.